Kaybolan Tarihin Canlandırılması: Kastamonu Akmanlar Konağı Rekonstrüksiyon Önerisi. - Aksoy, Ercan (Electronic Turkish Studies, 2022)
Traditional cultural properties are one of the elements that reflect the cultures of the settlements and the society, and convey them to future generations. Of the cultural properties, traditional houses are also important since they contain environmental and social values as well as individual values. However, structures that have lost their properties due to different reasons collapse and disappear as a result of failure to intervene in time. In this case, at least, there is a possibility to reconstruct them by preparing the surveys before the collapse of these structures. Although it is much more important to protect the structures in their original form, the reconstruction of the collapsed structures in accordance with the original is also a protection method. The survey of Akmanlar Mansion in the province of Kastamonu, Turkey, was prepared in 2018 and then the structure collapsed as a result of neglect and weathering conditions. In the study, a restitution proposal was made by using the survey drawings related to the collapsed mansion with the aim of its reconstruction. In the preparation of the survey, the traditional technique was used in combination with the optical laser scanner, and the structure was depicted with its whole system. In the restitution proposal, the data obtained from the surrounding structures were considered together with the data from the structure. A reconstruction proposal was made to maintain the texture and traditional features of the housing by rebuilding it in its former and original form. With the help of the present study, the cultural continuity of the housing together with both the individual and environmental values will be ensured. Furthermore, it is emphasized how important it is to document in order not to lose the values in case of delay in the protection of the structures.